Asuhan Keperawatan Keluarga Tn. S dengan Gangguan Sistem Muskuloskeletal : Gout Arthritis di Desa Kalibuntu Rt 04 Rw 03 Kecamatan Losari Kabupaten Brebes - Lulu Fatimatuzzahro; Esti Nur Janah; Siti Fatimah; Nur Umi Aminatusholihah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Non -communicable disease (PTM) is one of the increasing health problems in society every year and contributes to the largest proportion of death worldwide. According to a global status report on non -communicable diseases, non -communicable diseases can occur due to lack of exercise, smoking and malnutrition, which causes increased blood pressure, increased blood sugar levels and increased blood lipids. If not prevented, this increase will get worse and lead to chronic diseases such as hypertension, diabetes, cholesterol, dysplidemia, gout arthritis and obesity. The World Health Organization (WHO) reports that 40 million people worldwide suffer from non -communicable diseases, with the cause of cardiovascular disease, diabetes and injuries to be the main cause (Syam'ani, 2023).